Competência penal da justiça do trabalho: coerção penal: por um direito material trabalhista eficaz - Camila Almeida Peixoto Batista de Oliveira (2012)
The purpose of the research is to analyze the possibility of criminal judgment by the Labour Court under the perspective of philosophical belief of coercion as an instrument to guarantee Labour Law effectiveness. In the current conjuncture of global capitalism, the elision of workers rights is, in the eyes of many, an strategy for increasing profits and maximizing business competitiveness. The characterization of these conducts as a criminal offense symbolizes a social and legal repudiation. However, the non-application of sanctions by the common Court spreads impunity. From the premise that only criminal punishment can reverse this logic (considering that a strong constraint is enough to grant spontaneous fulfillment of Labour Law), the goal is to assure criminal jurisdiction as a counter-factual of labor infractions. The propose, therefore, is to affirm a new practical performance of the Labor Court, fully adequate to the current socio-economic cenary, which calls for an active and democratic state, guarantor of fundamental rights and the human dignity.